Diálogos e aprendizagens na formação em agronomia para assentados - Scalabrin, Rosemeri (2011)
This thesis aims to investigate the Agronomy course in the perspective of the graduation course for the settlers of the Universidade Federal do Pará- Marabá. This course requires a partnership with the social movements of the North region of the country, with the purpose to understand knowledge production and how learning process occurs from the point of interaction and reliable relationships which are established in the organization during the course. The base of theses studies is to reflect of how the dialogue and learning processes occurred during the Agronomy course and resulted in changing in the teachers behavior and in the other integrated members of the group and mainly in the graduating settlers students. These changings happens as a consenquence of the dialogue production between the most varied areas, different people and institutions which take collective decisions. I observe educational actions, researches, extention concepts of extension and also development researches presented in the educative actions discussed by Freire (1985), Simões (2001, 2003) e de Amartya Sen (2000). The theory in which I am basing these studies are based in Boaventura de Souza Santos Simões (2001, 2003) and Amartya Sen (2000). Methodologically I analyse knowledge production by sudying the thesis and scientific works related to rural education, social movements, university and higher education in the last 20 years. I analyze the scientific works of all settler students, and besides, I do open interviews with the students, as well as, with the teachers and the leaders of social movements (MST, FETAGRI, CPT, EFA/FATA). I organize and analyze all the speeches from the ecological knowledge as defined by Boaventura de Souza Santos (2006). Finally, I visit five towns of municipal districts of the southeast of Pará, which represents the final methodological part of the research, in order to verify in loco the practices of the experiments purposed as final activity of the Agronomy course. I organize the work in five areas composed by the occupational process and the initiatives which emerged from them; development model and the social and environmental consequences; I also organize the university role and the relationship established between people and institutions which gave origin to the Agronomy course of UFPA and the programs developed in the region; conjuncture of creation of the groups of settled students, curriculum, principles and focus on the course and the experienced actions; developed practices in the course and the relations of reliability experienced internally and externally to the Academy, the learning and dialogue promoted by the course. I believe that the dialogue has caused changes in the organization of the knowledge and in the educative practices of the teachers, as well as, in the socio-productive practices of the regressed settled students